Power quality assessment of novel multilevel and multistring inverters for electric vehicle applications - Sri Krishna Kumar Sampathkumar; Dhal Pradyumna Kumar (Institute of Advanced Engineering and Science, 2022)
The requirement and demand of electric vehicles is extravagantly increasing in the current era for avoiding pollutions and as well to overcome the consumptions of liquid fuels. Under this scenario, for the production and applicability of electric vehicles, inverters play a major role to render appropriate battery power supply for the perfect operation of the electric vehicle. This research study devises a novel modified multilevel inverter and a new multistring inverter designed by reducing the number of switches and enabling the effective operation of the electric vehicle. Both the developed multilevel and multistring inverter is analyzed with respect to their switching states, their output voltage and the evaluated harmonic distortion. For comparison, a sinusoidal alternating current voltage is considered as reference and all the newly modeled configurations are compared with that of the existing inverter models to prove their superiority. The switched states of the designed inverters as applicable for electric vehicles are examined to attain a logical analysis with respect to the duty cycle of the individual switches. The power quality assessment of the designed inverter models are guaranteed based on the minimized total harmonic distortion and on comparison with the other inverter models from the earlier state-of-the-art techniques.